Analysis of Word of Mouth and Social Media Marketing on Purchase Decisions with Brand Awareness as Intervening Variable at Mitrakuli.Id - Dicky Tanzila Suryanto; Cliff Kohardinata (Journal Research of Social Science, Economics, and Management, 2025)
Abstract. Indonesia is experiencing significant development in the infrastructure sector with a projected construction market growth of 5.48% by 2025. This trend is driving the increasing demand for project tool leasing as a cost and time efficient solution for small to medium-sized contractors. PT. Mitra Kuli Indonesia (Mitrakuli.id) is a newcomer in the project equipment rental business in East Java, especially Malang City. However, as a new brand, the company faces challenges in building a loyal customer base. Sales data shows revenue instability, which is allegedly caused by increased competition in the industry. Competitors fall into two categories: legacy companies that rely on Word Of Mouth (WOM) and new companies that leverage digital marketing. Previous studies have shown that Word Of Mouth plays a significant role in building customer trust, while digital marketing allows new companies to reach a wider audience and increase customer engagement. With so many competitors, Mitrakuli.id need to increase Brand Awareness to stay competitive. This study aims to analyze the influence of Word Of Mouth and Social Media Marketing on the decision to purchase project equipment rental services, with Brand Awareness as an intervening variable. The results of the research are expected to provide strategic insights for the industry in designing marketing strategies that are more effective and relevant to current market conditions.